Preparation method of antireflection coating system deposited on chalcogenide glass substrate

By plating a multi-layer membrane layer on the base of sulfur glass, it is difficult to meet the problem of high and low temperature environment and high-transmission rate of 3-5 μm infrared bands, and achieve efficient infrared transmission effects.

CN116282962BActive Publication Date: 2025-01-28安徽光智科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310348614.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-01-28
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The existing infrared optical coating technology is difficult to meet the requirements of high and low temperature environments and high transmittance in the 3-5μm infrared band.

Method used

The preparation method of plating diaphragm system on a sulfur glass base is used to control the thickness and deposition of each membrane layer by goughing on both sides of the sulfur glass base, including GE, ZNS, and YBF3 membrane layers. The rate, using ion source assisted steam plating technology to form an efficient diaphragm system.

Benefits of technology

The high transmission rate is maintained in high and low temperature environments, and the transmission rate of 3-5 μm infrared bands reaches more than 98 %, which meets the needs of high and low temperature environment and high radiation rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282962B_ABST
    Figure CN116282962B_ABST
Patent Text Reader

Abstract

A method for preparing an antireflection film system coated on a chalcogenide glass substrate comprises the following steps: S1, cleaning the surfaces of a chalcogenide glass substrate and a product as a lens; S2, placing the lens in a fixture, and hanging the fixture in a vacuum coating machine; S3, starting the vacuum coating machine to evacuate the vacuum, and cleaning the ion source; S4, maintaining the aforementioned vacuum degree, and evaporating a first Ge film layer on the corresponding surface of the lens; S5, evaporating a first ZnS film layer; S6, evaporating a second Ge film layer; S7, evaporating a second ZnS film layer; Step S1, step S2, step S3 and step S4, step S5, step S6, step S7, step S8, step S9, step S10, step S11, step S12, step S13, step S14, step S15, step S16, step S17, step S18, step S19, step S20, step S21, step S22, step S23, step S24, step S25, step S26, step S27, step S28, step S29, step S30, step S31, step S32, step S33, step S34, step S35, step S36, step S37, step S38, step S39, step S40, step S41, step S42, step S43, step S44, step S45
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the infrared field, and more particularly to a method for preparing an antireflection film system deposited on a chalcogenide glass substrate. Background Art

[0002] In the field of infrared optical coatings, chalcogenide glass offers unique advantages as a material for infrared lenses. Chalcogenide glass boasts high processing efficiency and can be precision molded, achieving a yield over 10 times greater than diamond turning, while its raw material cost is one-third that of single crystal germanium. Germanium single crystals are quite sensitive to temperature fluctuations, resulting in image instability. Chalcogenide glass, however, can withstand temperature fluctuations of 110°C, ranging from -40°C to 70°C, without any compromise, making it widely used in infrared imaging systems.

[0003] As infrared technology is increasingly used, the requirements for infrared coatings are becoming higher and higher. Therefore, it is necessary to further improve the anti-reflection film system coated on the chalcogenide glass substrate. Summary of the Invention

[0004] In view of the problems existing in the background technology, the purpose of the present disclosure is to provide a preparation method of an antireflection film system coated on a chalcogenide glass substrate, which can not only meet the requirements of working in high and low temperature environments but also meet the high transmittance requirements of the 3-5μm infrared band.

[0005] Therefore, a method for preparing an antireflection film system deposited on a chalcogenide glass substrate comprises the steps of:

[0006] S1, cleaning the surface of the accompanying plating sheet of the chalcogenide glass substrate and the product as the lens, wherein the thickness of the accompanying plating sheet of the chalcogenide glass substrate is 0.9-1.5 mm and the chalcogenide glass grade IG06 is used;

[0007] S2, put the cleaned lens including the accompanying coating sheet and the product into the fixture, and hang the fixture with the lens into the chamber of the vacuum coating machine. The temperature of the chamber is set to 120-130℃;

[0008] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1×10 -3 Pa, open the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.2-1.5A, and the emitter current is 1.3-1.5A;

[0009] S4, maintaining the aforementioned vacuum level, and evaporating a first Ge film layer on the corresponding surface of the lens. The deposition rate of the first Ge film layer is 0.3 nm / s, and the film thickness of the first Ge film layer is controlled to be 63 nm ± 3 nm. The evaporation is assisted by an ion source;

[0010] S5, evaporating a first ZnS film layer on the deposited first Ge film layer, with a deposition rate of the first ZnS film layer being 0.8 nm / s, and controlling the film thickness of the first ZnS film layer to be 123 nm ± 4 nm, using an ion source assisted evaporation method;

[0011] S6, evaporating a second Ge film layer on the plated first ZnS film layer, with a deposition rate of the second Ge film layer of 0.3 nm / s, controlling the film thickness of the second Ge film layer to be 307 nm ± 5 nm, and using an ion source assisted evaporation method;

[0012] S7, evaporating a second ZnS film layer on the deposited second Ge film layer, with a deposition rate of the second ZnS film layer being 0.8 nm / s and a film thickness of the second ZnS film layer being controlled to be 63 nm ± 3 nm, using an ion source assisted evaporation method;

[0013] S8, evaporating a third Ge film layer on the plated second ZnS film layer, with a deposition rate of the third Ge film layer of 0.3 nm / s, controlling the film thickness of the third Ge film layer to be 90 nm ± 3 nm, and using an ion source assisted evaporation method;

[0014] S9, evaporating a third ZnS film layer on the plated third Ge film layer, with a deposition rate of the third ZnS film layer being 0.8 nm / s, and controlling the film thickness of the third ZnS film layer to be 215 nm ± 5 nm, using an ion source assisted evaporation method;

[0015] S10, evaporating a YbF3 film layer on the plated third ZnS film layer, with a deposition rate of the YbF3 film layer of 0.6 nm / s and a film thickness of the YbF3 film layer controlled to be 300 nm ± 5 nm, using an ion source assisted evaporation method;

[0016] S11, evaporating a fourth ZnS film layer on the plated YbF3 film layer, with a deposition rate of the fourth ZnS film layer of 0.8 nm / s and a film thickness of the fourth ZnS film layer controlled to be 75 nm ± 3 nm, using an ion source assisted evaporation method;

[0017] S12, after the coating is completed, wait for the vacuum chamber to cool down to below 80°C and take out the lens with the corresponding surface coated;

[0018] S13, repeat steps S1 to S12, and sequentially evaporate a first Ge film layer, a first ZnS film layer, a second Ge film layer, a second ZnS film layer, a third Ge film layer, a third ZnS film layer, a YbF3 film layer, and a fourth ZnS film layer on the opposite side of the lens.

[0019] The beneficial effects of the present disclosure are as follows: in the preparation method of coating an antireflection film system on a chalcogenide glass substrate disclosed in the present disclosure, a first Ge film layer with a thickness of 63nm±3nm, a first ZnS film layer with a thickness of 123nm±4nm, a second Ge film layer with a thickness of 307nm±5nm, a second ZnS film layer with a thickness of 63nm±3nm, a third Ge film layer with a thickness of 90nm±3nm, a third ZnS film layer with a thickness of 215nm±5nm, a YbF3 film layer with a thickness of 300nm±5nm, and a fourth ZnS film layer with a thickness of 75nm±3nm are coated on both sides of a co-coating sheet of a chalcogenide glass substrate serving as a lens and a product. The eight film layers on each side will serve as the antireflection film system of the product. Based on the test of the co-coating sheet in the 3-5μm infrared band, the transmittance in the 3-5μm infrared band can reach more than 98%. In other words, the combination of the chalcogenide glass substrate and the eight film layers on each surface can not only meet the requirements of working in high and low temperature environments but also meet the high transmittance requirements of the 3-5μm infrared band. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a structural schematic diagram of coating an antireflection film system on both sides of a companion plate and a product including a chalcogenide glass substrate according to the preparation method of coating an antireflection film system on a chalcogenide glass substrate disclosed in the present invention.

[0021] Figure 2 This is a curve diagram of the transmittance of the accompanying plate of Example 1 in the 3-5 μm infrared band, in which antireflection films are coated on both sides. DETAILED DESCRIPTION

[0022] The accompanying drawings show embodiments of the present disclosure, and it will be understood that the disclosed embodiments are merely examples of the present disclosure, which can be implemented in various forms. Therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0023] [Preparation method of antireflection film system coated on chalcogenide glass substrate]

[0024] The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to the present disclosure comprises the following steps:

[0025] S1, cleaning the surface of the accompanying plating sheet of the chalcogenide glass substrate and the product as the lens, wherein the thickness of the accompanying plating sheet of the chalcogenide glass substrate is 0.9-1.5 mm and the chalcogenide glass grade IG06 is used;

[0026] S2, put the cleaned lens including the accompanying coating sheet and the product into the fixture, and hang the fixture with the lens into the chamber of the vacuum coating machine. The temperature of the chamber is set to 120-130℃;

[0027] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1×10 -3 Pa, open the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.2-1.5A, and the emitter current is 1.3-1.5A;

[0028] S4, maintaining the aforementioned vacuum level, and evaporating a first Ge film layer on the corresponding surface of the lens. The deposition rate of the first Ge film layer is 0.3 nm / s, and the film thickness of the first Ge film layer is controlled to be 63 nm ± 3 nm. The evaporation is assisted by an ion source;

[0029] S5, evaporating a first ZnS film layer on the deposited first Ge film layer, with a deposition rate of the first ZnS film layer being 0.8 nm / s, and controlling the film thickness of the first ZnS film layer to be 123 nm ± 4 nm, using an ion source assisted evaporation method;

[0030] S6, evaporating a second Ge film layer on the plated first ZnS film layer, with a deposition rate of the second Ge film layer of 0.3 nm / s, controlling the film thickness of the second Ge film layer to be 307 nm ± 5 nm, and using an ion source assisted evaporation method;

[0031] S7, evaporating a second ZnS film layer on the deposited second Ge film layer, with a deposition rate of the second ZnS film layer being 0.8 nm / s and a film thickness of the second ZnS film layer being controlled to be 63 nm ± 3 nm, using an ion source assisted evaporation method;

[0032] S8, evaporating a third Ge film layer on the plated second ZnS film layer, with a deposition rate of the third Ge film layer of 0.3 nm / s, controlling the film thickness of the third Ge film layer to be 90 nm ± 3 nm, and using an ion source assisted evaporation method;

[0033] S9, evaporating a third ZnS film layer on the plated third Ge film layer, with a deposition rate of the third ZnS film layer being 0.8 nm / s, and controlling the film thickness of the third ZnS film layer to be 215 nm ± 5 nm, using an ion source assisted evaporation method;

[0034] S10, evaporating a YbF3 film layer on the plated third ZnS film layer, with a deposition rate of the YbF3 film layer of 0.6 nm / s and a film thickness of the YbF3 film layer controlled to be 300 nm ± 5 nm, using an ion source assisted evaporation method;

[0035] S11, evaporating a fourth ZnS film layer on the plated YbF3 film layer, with a deposition rate of the fourth ZnS film layer of 0.8 nm / s and a film thickness of the fourth ZnS film layer controlled to be 75 nm ± 3 nm, using an ion source assisted evaporation method;

[0036] S12, after the coating is completed, wait for the vacuum chamber to cool down to below 80°C and take out the lens with the corresponding surface coated;

[0037] S13, repeat steps S1 to S12, and sequentially evaporate a first Ge film layer, a first ZnS film layer, a second Ge film layer, a second ZnS film layer, a third Ge film layer, a third ZnS film layer, a YbF3 film layer, and a fourth ZnS film layer on the opposite side of the lens.

[0038] In the preparation method of coating an antireflection film system on a chalcogenide glass substrate disclosed herein, a first Ge film layer with a thickness of 63nm±3nm, a first ZnS film layer with a thickness of 123nm±4nm, a second Ge film layer with a thickness of 307nm±5nm, a second ZnS film layer with a thickness of 63nm±3nm, a third Ge film layer with a thickness of 90nm±3nm, a third ZnS film layer with a thickness of 215nm±5nm, a YbF3 film layer with a thickness of 300nm±5nm, and a fourth ZnS film layer with a thickness of 75nm±3nm are coated on both sides of a co-coating sheet of a chalcogenide glass substrate serving as a lens and a product. The eight film layers on each side will serve as the antireflection film system of the product. Based on the test of the co-coating sheet in the 3-5μm infrared band, the transmittance in the 3-5μm infrared band can reach more than 98%. In other words, the combination of the chalcogenide glass substrate and the eight film layers on each surface can not only meet the requirements of working in high and low temperature environments but also meet the high transmittance requirements of the 3-5μm infrared band.

[0039] In the method for preparing an antireflection film system coated on a chalcogenide glass substrate disclosed herein, the total thickness of the eight film layers coated on each surface of the accompanying plate and the product of the chalcogenide glass substrate serving as a lens is 1236 nm ± 31 nm.

[0040] In the method for preparing an antireflection film system deposited on a chalcogenide glass substrate disclosed herein, the surface cleaning in step S1 is beneficial to improving the surface conditions of both surfaces of the accompanying coating sheet and the product, and helps to improve the bonding performance of both surfaces of the accompanying coating sheet and the product.

[0041] In the method for preparing an antireflection film system deposited on a chalcogenide glass substrate disclosed herein, the temperature of the chamber in step S2 helps to eliminate stress in the film layers on both sides of the accompanying plate and the product, and also helps to grow the film layers of the antireflection film system on both sides of the accompanying plate and the product.

[0042] In the disclosed method for preparing an antireflection film system deposited on a chalcogenide glass substrate, step S3 employs an ion source for cleaning. The bombardment and sputtering of argon ions ionized by the working gas argon remove impurities, oil molecules, and oxides adsorbed on the surface of the corresponding surfaces of the accompanying coating sheet and the product from the substrate surface, thereby significantly improving the interface state and facilitating improved bonding performance between the first Ge film layer and the corresponding surface of the chalcogenide glass substrate. Simultaneously, the bombardment of the argon ions on the corresponding surface of the chalcogenide glass substrate heats the corresponding surface of the chalcogenide glass substrate, facilitating the growth of the first Ge film layer and reducing the growth stress of the first Ge film layer.

[0043] In the method for preparing an antireflection film system deposited on a chalcogenide glass substrate disclosed herein, in steps S4 to S11, ion source assisted evaporation bombards the surface of the lens with ions to facilitate film growth, improve adhesion and hardness, and reduce film stress.

[0044] In the preparation method of coating an antireflection film system on a chalcogenide glass substrate disclosed herein, the first Ge film layer in step S3 has the smallest film thickness among the eight film layers, enabling a transition from the chalcogenide glass substrate to the first ZnS film layer using the thinnest transition layer.

[0045] It should be noted that in the method for preparing an antireflection film system deposited on a chalcogenide glass substrate disclosed herein, the accompanying plate is a plate with equal thickness and flat surfaces on both sides, and the shape and size of the product may be different from the accompanying plate based on actual needs.

[0046] In one example, in step S1 , the thickness of the accompanying coating of the chalcogenide glass substrate is 1.0 mm.

[0047] In one example, in step S1 , the lens surface is cleaned by ultrasonic waves or hand wiping.

[0048] In one example, in step S2 , the temperature of the chamber is set to 125° C.

[0049] In one example, in step S3 , the anode current is 1.2A and the emitter current is 1.5A.

[0050] In one example, in step S3 , the ion source is a Hall ion source.

[0051] In one example, in step S4, the thickness of the first Ge film layer is controlled to be 63 nm; in step S5, the thickness of the first ZnS film layer is controlled to be 123 nm; in step S6, the thickness of the second Ge film layer is controlled to be 307 nm; in step S7, the thickness of the second ZnS film layer is controlled to be 63 nm; in step S8, the thickness of the third Ge film layer is controlled to be 90 nm; in step S9, the thickness of the third ZnS film layer is controlled to be 215 nm; in step S10, the thickness of the YbF3 film layer is controlled to be 300 nm; and in step S11, the thickness of the fourth ZnS film layer is controlled to be 75 nm.

[0052] In one example, in step S4, step S6, and step S8, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: a neutralization current of 0.5 A, argon is used to form the neutralization gas, and the flow rate of the neutralization gas is 10 sccm; the anode voltage of the ion source is 150 V, the anode current is 1.2 A, argon is used as the working gas, and the flow rate of the argon is 100 sccm.

[0053] In one example, in step S5, step S7, step S9 and step S11, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: the neutralization current is 0.5A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 10sccm, the anode voltage of the ion source is 180V, the anode current is 1.8A, argon is used as the working gas, and the flow rate of the argon is 100sccm.

[0054] In one example, in step S10, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: a neutralization current of 0.5 A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 10 sccm, the anode voltage of the ion source is 120 V, the anode current is 1.2 A, argon is used as the working gas, and the flow rate of the argon is 100 sccm.

[0055] In the above example using a neutralizer, the ionized argon gas from the ion source forms a near-plasma. However, this plasma may contain excess charged ions. The argon gas in the neutralizer ionizes into electrons, which neutralize the excess charged ions produced by the ion source. This eliminates the effect of the charged ions on the evaporated film, thereby ensuring the quality of each film layer assisted by ion source evaporation. Therefore, this effect can be achieved with only a very small flow ratio (1 / 10) of neutralizing gas to working gas.

[0056] In one example, in step S4 , step S6 , and step S8 , the evaporation is performed by electron beam evaporation; and in step S5 , step S7 , step S9 , step S11 , and step S10 , the evaporation is performed by resistance heating evaporation.

[0057] [test]

[0058] Example 1

[0059] The method for preparing an antireflection film system deposited on a chalcogenide glass substrate comprises the following steps:

[0060] S1, using ultrasonic cleaning to clean the surface of the accompanying plating sheet of the chalcogenide glass substrate and the product, wherein the thickness of the accompanying plating sheet of the chalcogenide glass substrate is 1.0 mm and the chalcogenide glass grade is IG06;

[0061] S2: Place the cleaned lens including the accompanying coating sheet and the product into a fixture, and then hang the fixture with the lens in place into the chamber of a vacuum coating machine. The temperature of the chamber is set to 125°C. The vacuum coating machine is a vacuum coating machine with a Hall ion source equipped with a neutralizer, manufactured and sold by Chengdu Siwork Vacuum Technology Co., Ltd. The Hall ion source equipped with a neutralizer is purchased from Boton Optoelectronics Technology Co., Ltd.

[0062] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1×10 -3 Pa, open the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.2A, and the emitter current is 1.5A;

[0063] S4, maintaining the aforementioned vacuum level, and depositing a first Ge film layer on the corresponding surface of the lens. The deposition rate of the first Ge film layer is 0.3 nm / s, and the film thickness of the first Ge film layer is controlled to be 63 nm. The deposition is carried out by electron beam evaporation.

[0064] S5, vapor-depositing a first ZnS film layer on the plated first Ge film layer, with a deposition rate of the first ZnS film layer being 0.8 nm / s, controlling the film thickness of the first ZnS film layer to be 123 nm, and adopting a resistance heating evaporation method;

[0065] S6, evaporating a second Ge film layer on the plated first ZnS film layer, with a deposition rate of the second Ge film layer of 0.3 nm / s, controlling the film thickness of the second Ge film layer to be 307 nm, and adopting electron beam evaporation;

[0066] S7, vapor-depositing a second ZnS film layer on the deposited second Ge film layer, with a deposition rate of the second ZnS film layer being 0.8 nm / s, and controlling the film thickness of the second ZnS film layer to be 63 nm, using a resistance heating evaporation method;

[0067] S8, vapor-depositing a third Ge film layer on the plated second ZnS film layer, with a deposition rate of the third Ge film layer of 0.3 nm / s and a thickness of the third Ge film layer of 90 nm, using electron beam evaporation;

[0068] S9, vapor-depositing a third ZnS film layer on the plated third Ge film layer, with a deposition rate of the third ZnS film layer being 0.8 nm / s, and controlling the film thickness of the third ZnS film layer to be 215 nm, using a resistance heating evaporation method;

[0069] S10, vapor-depositing a YbF3 film layer on the plated third ZnS film layer, with a deposition rate of the YbF3 film layer being 0.6 nm / s and a film thickness of the YbF3 film layer being controlled to be 300 nm, using a resistance heating evaporation method;

[0070] S11, vapor-depositing a fourth ZnS film layer on the plated YbF3 film layer, with a deposition rate of the fourth ZnS film layer of 0.8 nm / s and a thickness of the fourth ZnS film layer of 75 nm, using a resistance heating evaporation method;

[0071] S12, after the coating is completed, wait for the vacuum chamber to cool down to below 80°C and take out the lens with the corresponding surface coated;

[0072] S13, repeating steps S1 to S11, sequentially depositing a first Ge film layer, a first ZnS film layer, a second Ge film layer, a second ZnS film layer, a third Ge film layer, a third ZnS film layer, a YbF3 film layer, and a fourth ZnS film layer on the opposite side of the lens;

[0073] In steps S4, S6, and S8, the parameters of the neutralizer are as follows: a neutralization current of 0.5 A, argon gas is used as the neutralization gas, the flow rate of the neutralization gas is 10 sccm, the anode voltage of the ion source is 150 V, the anode current is 1.2 A, argon gas is used as the working gas, and the flow rate of the argon gas is 100 sccm;

[0074] In steps S5, S7, S9, and S11, the parameters of the neutralizer are as follows: a neutralization current of 0.5 A, argon gas is used as the neutralization gas, the flow rate of the neutralization gas is 10 sccm, the anode voltage of the ion source is 180 V, the anode current is 1.8 A, argon gas is used as the working gas, and the flow rate of the argon gas is 100 sccm;

[0075] In step S10, the parameters of the neutralizer are: neutralization current of 0.5A, argon gas is used to form the neutralization gas, the flow rate of the neutralization gas is 10sccm, the anode voltage of the ion source is 120V, the anode current is 1.2A, argon gas is used as the working gas, and the flow rate of argon gas is 100sccm.

[0076] The structure of the lens prepared in Example 1 with eight layers of film on both sides is as follows Figure 1 As shown schematically, Figure 2 The transmittance curve of the accompanying coating sheet prepared in Example 1 and the eight layers of film coated on both sides (constituting the anti-reflection film system) is shown. Figure 2It can be seen that in the 3-5 μm band, the transmittance (arithmetic mean) can reach more than 98%.

[0077] The overall performance of the accompanying plating sheet and the eight layers of film plated on both sides is tested.

[0078] Water bubble test: The accompanying plating sheet prepared in Example 1, together with the eight film layers plated on both sides, was subjected to a water bubble test with tap water for 10 minutes. No eight film layers on each side were found to fall off the accompanying plating sheet, nor were the eight film layers on each side found to crack.

[0079] Adhesion test: After the blister and salt spray tests with tap water were completed, 3M tape was manually applied to the fourth ZnS film layer on each side of the accompanying plating sheet and the tape was pulled in the direction opposite to the pasting end. The eight film layers were not pulled up.

[0080] The water bubble test and tape pulling test show that the eight layers of film on both sides of the plating sheet have good adhesion.

[0081] Thermal shock test: Thermal shock was conducted in a high and low temperature chamber at a temperature range of -40°C to 85°C for 24 hours. No eight layers of film on each side of the accompanying plating sheet were found to fall off or crack.

[0082] Constant temperature and humidity test: In a constant temperature and humidity chamber at 50°C and 95% relative humidity for 48 hours, no eight layers of coating on each side of the accompanying plating sheet were found to be falling off or cracking.

[0083] Salt spray test: After 48 hours of neutral salt spray test, no eight layers of film on each side of the accompanying plating sheet were found to fall off from the accompanying plating sheet, nor were any eight layers of film on each side of the accompanying plating sheet found to be cracked.

[0084] Low temperature test: in a low temperature box, at -40℃ for 48 hours, the eight layers of film on each side of the accompanying plating sheet were not found to fall off from the accompanying plating sheet, nor were the eight layers of film on each side of the accompanying plating sheet found to be cracked on the accompanying plating sheet.

[0085] High temperature test: at a high temperature of 85°C for 48 hours, no eight layers of film on each side of the accompanying plating sheet were found to fall off from the accompanying plating sheet, nor were any eight layers of film on each side of the accompanying plating sheet found to crack.

[0086] The above detailed description is used to describe a number of exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein may be combined to form multiple additional combinations that are not shown for the sake of brevity.

Claims

1. A method for preparing an antireflection film system coated on a chalcogenide glass substrate, characterized in that: Includes steps: S1, cleaning the surfaces of the accompanying plating sheet of the chalcogenide glass substrate and the product as the lens, wherein the thickness of the accompanying plating sheet of the chalcogenide glass substrate is 0.9-1.5 mm and the accompanying plating sheet of the chalcogenide glass substrate adopts the chalcogenide glass grade IG06; S2, put the cleaned lens including the accompanying coating sheet and the product into the fixture, and hang the fixture with the lens into the cavity of the vacuum coating machine, and set the temperature of the cavity to 120-130℃; S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1×10 -3 Pa, turn on the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.2-1.5A, and the emitter current is 1.3-1.5A; S4, maintaining the aforementioned vacuum degree, evaporating a first Ge film layer on the corresponding surface of the lens, the deposition rate of the first Ge film layer is 0.3nm / s, the film thickness of the first Ge film layer is controlled to be 63nm±3nm, and the ion source is used to assist the evaporation; S5, evaporating a first ZnS film layer on the plated first Ge film layer, the deposition rate of the first ZnS film layer is 0.8 nm / s, the film thickness of the first ZnS film layer is controlled to be 123 nm±4 nm, and the evaporation is assisted by an ion source; S6, evaporating a second Ge film layer on the plated first ZnS film layer, the deposition rate of the second Ge film layer is 0.3 nm / s, the film thickness of the second Ge film layer is controlled to be 307 nm±5 nm, and the evaporation is assisted by an ion source; S7, evaporating a second ZnS film layer on the plated second Ge film layer, the deposition rate of the second ZnS film layer is 0.8 nm / s, the film thickness of the second ZnS film layer is controlled to be 63 nm±3 nm, and the ion source is used to assist the evaporation; S8, evaporating a third Ge film layer on the plated second ZnS film layer, the deposition rate of the third Ge film layer is 0.3 nm / s, the film thickness of the third Ge film layer is controlled to be 90 nm±3 nm, and the evaporation is assisted by an ion source; S9, evaporating a third ZnS film layer on the plated third Ge film layer, the deposition rate of the third ZnS film layer is 0.8 nm / s, the film thickness of the third ZnS film layer is controlled to be 215 nm±5 nm, and the evaporation is assisted by an ion source; S10, evaporating a YbF3 film layer on the plated third ZnS film layer, the deposition rate of the YbF3 film layer is 0.6 nm / s, the film thickness of the YbF3 film layer is controlled to be 300 nm±5 nm, and the evaporation is assisted by an ion source; S11, evaporating a fourth ZnS film layer on the plated YbF3 film layer, the deposition rate of the fourth ZnS film layer is 0.8nm / s, the film thickness of the fourth ZnS film layer is controlled to be 75nm±3nm, and the evaporation is assisted by an ion source; S12, after the plating is completed, wait for the vacuum chamber to cool down to below 80°C and take out the lens with the corresponding surface plated; S13, repeating steps S1 to S12, and sequentially depositing a first Ge film layer, a first ZnS film layer, a second Ge film layer, a second ZnS film layer, a third Ge film layer, a third ZnS film layer, a YbF3 film layer and a fourth ZnS film layer on the other side of the lens; In the 3-5μm band, the transmittance of the prepared accompanying coating sheet together with the eight layers of film coated on both sides reaches more than 98%, and it has passed the bubble test, adhesion test, hot and cold shock test, constant temperature and humidity test, salt spray test, low temperature test and high temperature test. in, Water bubble test: The prepared accompanying plated sheet together with the eight layers of film plated on both sides was subjected to a water bubble test with tap water for 10 minutes; Adhesion test: After the blister and salt spray tests with tap water are completed, 3M tape is pasted on the fourth ZnS film layer on each side of the co-plating sheet by hand and the tape is pulled in the direction opposite to the pasting end; Thermal shock test: in a high and low temperature chamber, perform thermal shock in the range of -40°C to 85°C for 24 hours; Constant temperature and humidity test: in a constant temperature and humidity chamber, 50°C, 95% relative humidity for 48h; Salt spray test: neutral salt spray test for 48h; Low temperature test: in a low temperature box, -40°C for 48h, High temperature test: in a high temperature box, 85°C for 48h.

2. The method for preparing an antireflection film system coated on a chalcogenide glass substrate according to claim 1, characterized in that: In step S1, the thickness of the accompanying coating of the chalcogenide glass substrate is 1.0 mm; In step S1, the surface of the lens is cleaned by ultrasonic wave or hand wiping.

3. The method for preparing an antireflection film system coated on a chalcogenide glass substrate according to claim 1, characterized in that: In step S2, the temperature of the chamber is set to 125°C.

4. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S3, the anode current is 1.2A and the emitter current is 1.5A.

5. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S3, the ion source is a Hall ion source.

6. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S4, the film thickness of the first Ge film layer is controlled to be 63 nm; In step S5, the film thickness of the first ZnS film layer is controlled to be 123 nm; In step S6, the thickness of the second Ge film layer is controlled to be 307 nm; In step S7, the film thickness of the second ZnS film layer is controlled to be 63 nm; In step S8, the thickness of the third Ge film layer is controlled to be 90 nm; In step S9, the film thickness of the third ZnS film layer is controlled to be 215 nm; In step S10, the thickness of the YbF3 film layer is controlled to be 300 nm; In step S11 , the film thickness of the fourth ZnS film is controlled to be 75 nm.

7. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S4, step S6 and step S8, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: the neutralization current is 0.5A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 10sccm, the anode voltage of the ion source is 150V, the anode current is 1.2A, argon is used as the working gas, and the flow rate of argon is 100sccm.

8. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S5, step S7, step S9 and step S11, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: the neutralization current is 0.5A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 10sccm, the anode voltage of the ion source is 180V, the anode current is 1.8A, argon is used as the working gas, and the flow rate of argon is 100sccm.

9. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S10, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: a neutralization current of 0.5A, argon gas is used to form the neutralization gas, the flow rate of the neutralization gas is 10sccm, the anode voltage of the ion source is 120V, the anode current is 1.2A, argon gas is used as the working gas, and the flow rate of argon gas is 100sccm.

10. The method for preparing an antireflection film system deposited on a chalcogenide glass substrate according to claim 1, characterized in that: In step S4, step S6 and step S8, the evaporation is performed by electron beam evaporation; In step S5 , step S7 , step S9 , step S11 , and step S10 , the vapor deposition is performed by resistance heating evaporation.

Citation Information

Patent Citations

  • Film system of infrared double-waveband antireflection film system and plating method thereof

    CN101620280A

  • Preparation method of chalcogenide glass 8-12 [mu] m waveband high-durability antireflection film

    CN115368031A

  • Use medium -long wave infrared anti -reflection film of germanium as basement

    CN206741013U